The effect of immune selection on the structure of the meningococcal opa protein repertoire. - Callaghan, M; Buckee, C; Jolley, K; Kriz, P; Maiden, M; Gupta, S (Public Library of Science, 2008)
The opa genes of the Gram negative bacterium Neisseria meningitidis encode Opacity-associated outer membrane proteins whose role is to promote adhesion to the human host tissue during colonisation and invasion. Each meningococcus contains 3-4 opa loci, each of which may be occupied by one of a large number of alleles. We analysed the Opa repertoire structure in a large, well-characterised collection of asymptomatically carried meningococci. Our data show an association between Opa repertoire and meningococcal lineages similar to that observed previously for meningococci isolated from cases of invasive disease. Furthermore, these Opa repertoires exhibit discrete, non-overlapping structure at a population level, and yet low within-repertoire diversity. These data are consistent with the predictions of a mathematical model of strong immune selection upon a system where identical alleles may occupy different loci.